2019
DOI: 10.1117/1.jbo.24.8.086002
|View full text |Cite
|
Sign up to set email alerts
|

Method for improving the spatial resolution of narrow x-ray beam-based x-ray luminescence computed tomography imaging

Abstract: Method for improving the spatial resolution of narrow x-ray beam-based x-ray luminescence computed tomography imaging," J.Abstract. X-ray luminescence computed tomography (XLCT) is an emerging hybrid imaging modality which has the potential for achieving both high sensitivity and spatial resolution simultaneously. For the narrow x-ray beam-based XLCT imaging, based on previous work, a spatial resolution of about double the x-ray beam size can be achieved using a translate/rotate scanning scheme, taking step si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
(50 reference statements)
0
18
0
Order By: Relevance
“…In this work, we have proposed and investigated a continuous scanning strategy for narrow x-ray beam based XLCT imaging to improve upon the long imaging time. Compared with our previous studies, here we were able to perform a 6-projection transverse scan in 82 secs including all stage movements compared with 292.8 secs as in [11] (also including stage movements), an approximately 3.5 times reduction in scan time. Moreover, we were able to maintain the high-spatial resolution capabilities of this method and were able to successfully separate both targets with an EtE distance of 0.2 mm for all four cases while maintaining a good DICE similarity coefficient for all reconstructions as seen in Figs.…”
Section: Discussionmentioning
confidence: 84%
“…In this work, we have proposed and investigated a continuous scanning strategy for narrow x-ray beam based XLCT imaging to improve upon the long imaging time. Compared with our previous studies, here we were able to perform a 6-projection transverse scan in 82 secs including all stage movements compared with 292.8 secs as in [11] (also including stage movements), an approximately 3.5 times reduction in scan time. Moreover, we were able to maintain the high-spatial resolution capabilities of this method and were able to successfully separate both targets with an EtE distance of 0.2 mm for all four cases while maintaining a good DICE similarity coefficient for all reconstructions as seen in Figs.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, we have found that the spatial resolution of FXLT can be improved further by reducing the scanning step size as shown by our numerical simulations. Thus, we expect the designed FXLT imaging system may achieve a spatial resolution of 94 μm with 1.6 times improvement by using a scanning step size of 18.5 μm which is a quarter of the beam size as suggested by our recent paper (14).…”
Section: Discussionmentioning
confidence: 91%
“…Recently, we have found that the spatial resolution of FXLT imaging can be further improved by reducing the scanning step size. All the details of this method have been reported in (14). Here, we briefly describe a set of numerical simulations to demonstrate the efficacy of our proposed method.…”
Section: Fxlt Numerical Simulations With the Reduced Scanning Step Sizementioning
confidence: 99%
See 1 more Smart Citation
“…First, the new scanner’s x-ray beam diameter is much smaller than the previous scanner (49.9 versus ), which will allow for higher spatial resolution capabilities. From our previous reports, 5 , 27 , 28 we can estimate the spatial resolution of the designed FXLT scanner to be about . Next, the use of four highly sensitive PMTs (H7422-50) to detect the emitted optical signals will allow for much more sensitive setup than previously where only one PMT was used.…”
Section: Discussionmentioning
confidence: 99%